ChemInform Abstract: A Convenient Catalytic Asymmetric Conjugate Addition Reaction to Enones Using Alkylzirconium Reagents. Issue 8 (25th February 2014) - Maksymowicz, Rebecca M.; Sidera, Mireia; Roth, Philippe M. C.; Fletcher, Stephen P.
Abstract Alkylmetal species generated in situ from alkenes and the Schwartz reagent undergo enantioselective 1, 4‐conjugate addition to enones in the presence of a chiral copper complex as catalyst.